Improving selectivity of gold nanoparticles for glycerol electro-oxidation via interaction with non-noble metals - Thia, Larissa Yi Ping (2017)
This thesis begins by examining the current state of the art for glycerol electro-oxidation. Extensive research has been carried out to determine the effect of size, morphology, shape, support, experimental conditions and catalyst preparation methods on the catalytic performance of both Au and Pt based catalysts. While the effect of non-noble metal promoters has been relatively well studied for Pt group catalysts, the same cannot be said for Au based catalysts. Thus, the research work presented in this thesis aims to demonstrate how the selectivity of carbon supported Au nanoparticles for glycerol electro-oxidation can be improved via interaction of Au/C with non-noble metals.